GANGGUAN OTAK YANG BERKAITAN DENGAN PROSES BELAJAR - T, Marlini; BJ, Jusmiwarti (STKIP Pesisir Selatan, 2025)
Reason is the primary tool for learning. Learning is the process of understanding, analyzing, and then drawing conclusions. This learning process is a complex activity that involves the interaction of various systems in the brain, including attention (cognitive), memory, language, and the execution of cognitive functions. Brain disorders, both developmental and acquired, have a significant impact on an individual's cognitive abilities in the learning process. Essential cognitive functions such as attention, memory, language, and executive function are greatly affected by certain neurological conditions such as dyslexia, ADHD, autism, traumatic brain injury, and disorders due to brain infections. This article aims to identify the types of brain disorders that affect learning, analyze the specific impact on cognitive function, and formulate intervention strategies that can be applied. Intervention approaches include educational strategies based on differentiation and Individualized Education Program (IEP), therapeutic interventions such as speech and occupational therapy. With a comprehensive understanding of neurological conditions and individual needs of learners, the learning process can be optimized in an inclusive and adaptive manner.